Collective storytelling of common architecture: Arquitectura Aqui in Portugal and Spain - Agarez, R. C.; Inglez de Souza, D. (Jaap Bakema Study Center — Building Data: Architecture, Memory and New Imaginaries, 2022)
Conference organised by Dirk van den Heuvel, Fatma Tanis and Bing van der Meer (TU Delft). Proceedings available for download online at https://nieuweinstituut.nl/en/events/building-data (Publication without ISBN). Digital archives can be open laboratories for knowledge production and for new forms of intellectual and cultural examination of the built environment. Open is the key qualifier here: Open to whom? Whose archives are these? Who are their gatekeepers? What content are they open to? Does open access, on its own, guarantee the creation of a meaningful laboratory for knowledge production? Can the production itself be open? Knowledge of architecture and the built environment is generally narrow and exclusive: for the twentieth century, much of the research and writing behind it is based on canonical works (most in the ‘global North’) and very little on the common buildings and ensembles that frame community lives in unassuming ways – ‘common’ objects both in that they were meant to serve collective purposes and have not been seen, in art-historical, style-focused readings, as deserving attention. Even canonical works are largely narrated in specialised dissemination forums, confined by the rarefied language of experts. If storytelling avantgarde buildings to ‘lay’ audiences is a challenge for most, how about more mundane structures? Common pieces are, in fact, seldom seen as architecture at all in most contexts, even by designers. This widens the gap between the world of architects and the communities they exist to serve – a gap that has recurrently assailed the conscience of architectural thinkers, from contextualists to postmodernists and beyond. We believe that digital archives constructed as open laboratories for knowledge production can help bridge this gap, and bring architecture closer to local communities, if they are collectively generated: the paper discusses this possibility, its promise and challenges, based on a concrete example. Our research, dissemination and public engagement project Arquitectura Aqui. Community, Proximity, Action: Housing and Collective Facilities in Portugal and Spain 1939-1985 is grounded on a purpose-built digital archive: a new open-access information system where existing data (historical, material, technical and socio-cultural) is collected from mostly analogic, national, regional and local sources, filtered and combined in novel readings using layperson-friendly language and turned into storytelling vignettes on peripheral communities. This ongoing collective effort in architectural and urban history making and dissemination incorporates contributions from local actors – users, promoters, enablers and researchers – and seeks to respond to their input and concerns. Our focus on common objects aims at extending the use life of sturdy, pragmatic buildings that fulfil the essential needs of historically deprived communities, ranging from villages on remote locations that experienced desertification and deindustrialisation processes to towns in metropolitan and coastal areas. Our intention is to understand communities in a comprehensive approach, including in our sample every single building or space dedicated to collective use built within the proposed timeframe. Seeking to avoid a patronizing stance and conventional value-granting hierarchies, we cocreate this history to encourage its appropriation and inform local management, retain and reuse initiatives, countering the unsustainable, resource-exhausting trend to pull down and replace these structures that is still prevalent in Portugal and Spain.